Differences in sheep and goats milk microbiological profile between conventional and organic farming systems in Greece. Issue 2 (15th March 2017) - Malissiova, Eleni; Papadopoulos, Theofilos; Kyriazi, Aikaterini; Mparda, Maria; Sakorafa, Christina; Katsioulis, Antonios; Katsiaflaka, Anna; Kyritsi, Maria; Zdragas, Antonios; Hadjichristodoulou, Christos
Abstract : The aim of this study was to examine differences in the microbiological profile and antimicrobial resistance of bacteria isolated from milk from organic and conventional sheep and goat farms. Twenty-five organic and 25 conventional sheep and goat farms in the region of Thessaly, Greece participated in this study. A standardised detailed questionnaire was used to describe farming practices. A total of 50 samples were collected and analysed for total viable count (TVC), total coliform count (TCC) and somatic cell count (SCC), while Staphylococcus aureus and Escherichia coli were isolated using standard methods. Isolates were identified at species level by Api-test and Matrix-Assisted Laser Desorption/Ionisation-Time of Flight Mass Spectrometry (MALDI-TOF MS). Susceptibility to a panel of 20 for E. coli and 16 for S. aureus antimicrobials was determined by the agar dilution method. Pulsed Field Gel Electrophoresis (PFGE) was performed for S. aureus and E. coli isolates to determine predominant clones. Lower counts of TVC, TCC and SCC were identified in milk from the organic farms, possibly due to differences in the hygienic farming practices found on those farms. API-tests and MALDI-TOF MS showed no significant differences in the S. aureus and E. coli isolates. Overall, antimicrobial resistance rates were low, while a statistically higher percentage was estimated among strains originating from conventional farms in comparison with organic farms, possibly due to the restriction of antibiotic use in organic farming. PFGE revealed diversity among S. aureus and E. coli populations in both organic and conventional farms indicating circulation of 2–3 main clones changing slightly during their evolution. Consequently, there is evidence that milk from the organic farms presents a better microbiological profile when compared with milk from conventional farms.